Traceability technology, halal logistics brand and logistics performance: Religious beliefs and beyond - Fernando, Yudi; Wahyuni-TD, Ika Sari; Abideen, Ahmed Zainul; Mergeresa, Fineke (Emerald Publisher, 2022)
Purpose: The purpose of this study is to investigate the impact of Halal traceability technology usage on Halal logistics performance with a Halal logistics brand as a mediator. Design/methodology/approach; An online survey was conducted to gather responses from logistics service providers (LSPs), including strategic logistics units (manufacturing/brand owners) in Malaysia, which offer Halal logistics services. Findings; Halal traceability technology system and Halal traceability training are two critical domains to strengthen market recognition of Halal logistics brand for LSPs. The study found that the Halal logistics brand played a mediating role in connecting the usage of Halal traceability technology and logistics performance. Practical implications; The logistics industry needs to focus on Halal logistics services as a unique proposition. The ability of LSPs to build a Halal logistics brand thru traceability technology had created positive impressions for clients. LSPs must consistently engage in Halal training and remain technologically alert to build Halal brand value. Halal-based strategic branding will assist an LSP to stand out among its competitors. Originality/value: Even though Halal branding has been studied widely, little attention has been given to how the usage of Halal traceability technology can improve Halal logistics branding and logistics operational performance. The result suggests that LSPs need to build a Halal logistics brand and design a proper logistics business strategy to target Sharia compliance-oriented consumers.